INFORMATION USE ABOUT THE LEVEL OF AIRCRAFT FLIGHTS GROUND PROVISION TO PLAN AIR TRAFFIC - D. A. Zatuchny; J. V. Slad (Научный вестник МГТУ ГА, 2016)
The given article considers the task of building up the best aircraft route on the basis of information about the level of flight ground provision. Disadvantages of traditional radar surveillance facilities are given. Four types of Russian Federation aerospace depending on the level of ground radio flight provision are considered. Relevance of selecting an aircraft route from the view of necessity to plan aerospace is substantiated. The formula to calculate probabilities of obtaining not correct aircraft navigation data is given. The analysis of errors arising while building up the aircraft route linked with both operational navigation and communication equipment faults as well as with a human factor is carried out. Formulas of wrong route selecting probability when an aircraft track changes or is maintained are suggested. A generalized weighted index of losses on the basis of various factors affecting an aircraft track change is introduced. Importance of these factors are considered. A rule of aircraft transition to the next route point is formulated. The conclusion is made which route is the most rational in case of following the rule of route selecting at every flight stage. Practical recommendations which can be used to solve conflict between aircraft cruising under the given rule are suggested.